Penelitian pemanfaatan kulit sapi mentah dari nusa tenggara barat untuk kulit boks - Suliestiyah Wiryodiningrat (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1992)
The aim of this study was to identify of the quality upper leather made from dry cow hide taken from West Nusa Tenggara either of leather produced before or after being provided a technical assistance, were compared to them taken from Java. It was carried out by tanning both kinds of hides using selected IRDLAI tanning method. The upper leather produced in this research were physically tested (water absorption, tensile strength, flexibility and bursting strength), chemically tested (water content, ash content, Cr2O3 content, fat content and pH), as well as organoleptic inspection. The physical and chemical tests were six time repeated. A consclusion could be drawn from the organoleptic test result that the quality of Java upper leather were better compared to them of West Nusa Tenggara either before or after having technical assistance, while the quality of upper leathers after having technical guidance by IRDLAI were considered better compared to them before having it. The test result also shown that there was significant difference on fat, water and ash contents, bursting strength of upper leathers, the dry cow hides of which were taken from West Nusa Tenggara, either before or after having technical assistance. INTISARI Penelitian ini bertujuan untuk mengetahui mutu kulit boks dengan bahan baku kulit sapi mentah kering dari Nusa Tenggara Barat, baik sebelum maupun sesudah pembinaan dibandingkan dengan mutu kulit boks dengan bahan baku kulit sapi mentah kering dari pulau Jawa. Penelitian dilaksanakan dengan mengolah kulit mentah kering dari Nusa Tenggara Barat sebelum pembinaan dan sesudah pembinaan dan kulit mentah kering dari pulau Jawa menjadi kulit boks dengan metoda penyamakan kulit dari BBKKP. Dari hasil penyamakan kulit boks, kemudian masing-masing diuji sifat-sifat fisis (daya serap air, kekuatan tarik, kemuluran dan daya letup) dengan 6 replikasi (ulangan); sifat-sifat kimia (kadar air, kadar abu, kadar Cr2O3, kadar lemak dan pH) dengan replikasi serta diuji secara organoleptis. Dari hasil uji secara organoleptis ternyata kulit boks asal dari Pulau Jawa lebih baik dibanding dengan kualitas kulit boks asal dari Nusa Tenggara Barat baik sebelum maupun sesudah pembinaan. Sedangkan kualitas kulit boks asal dari kulit Nusa Tenggara sesudah pembinaan lebih baik dibanding kualitas kulit boks asal kulit dari Nusa Tenggara Barat sebelum pembinaan. Dari hasil penelitian menunjukkan terhadap perbedaan nyata untuk kadar lemak, kadar air, kadar abu, daya letup kulit boks yang berasal dari kulit Nusa Tenggara Barat, sebelum dan sesudah pembinaan.